COVID-19 effect: Profile of student learning motivation during online learning - Mertasari, Ni Made Sri; Paraniti, Anak Agung Inten; Mahardika, Putu Agung (Nurture, 2023)
Purpose: This study aims to describe the profile of students' learning motivation in online learning and compare intrinsic motivation and extrinsic motivation. Furthermore, the research also seeks to examine the development of intrinsic and extrinsic motivation over time during online learning. Design/Methodology/Approach: This survey research was conducted for mathematics learning at the Vocational High School level, involving a sample of 218 students selected by multistage random sampling technique. Questionnaires were administered periodically three times at an interval of six weeks. Data were analyzed using profile analysis. Findings: The analysis revealed that the intrinsic and extrinsic dimensions of students' learning motivation tend to be parallel, with the intrinsic dimension being higher than the extrinsic dimension. The period of time also affects the development of students' learning motivation, both for the intrinsic and extrinsic dimensions. Conclusion: The study highlights the importance of independent learning activities in online learning, which tend to develop and encourage the growth of internal motivation, essential for lifelong learning. Teachers are recommended to apply various learning theories in the digital era to increase students' internal and external motivation. In addition to well-designed learning materials, the effectiveness of online learning also depends on motivating interactions between instructors and students. Well-designed materials supported by a variety of communication media make online learning very beneficial.